Novel chemically modified bacterial cellulose nanocomposite as potential biomaterial for stem cell therapy applications - Acasigua, Gerson Arisoly Xavier; de Olyveira, Gabriel Molina [UNESP]; Costa, Ligia Maria Manzine; Braghirolli, Daikelly Iglesias; Fossati, Anna Christina Medeiros; Guastaldi, Antonio Carlos [UNESP]; Pranke, Patricia; Daltro, Gildásio de Cerqueira; Basmaji, Pierre (Bentham Science Publishers, 2014)
Bacterial cellulose (BC) has become established as a remarkably versatile biomaterial and can be used in a wide variety of applied scientific applications, especially for medical devices. In this work, the bacterial cellulose fermentation process is modified by the addition of hyaluronic acid and gelatin (1% w/w) to the culture medium before the bacteria is inoculated. Hyaluronic acid and gelatin influence in bacterial cellulose was analyzed using Transmission Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). Adhesion and viability studies with human dental pulp stem cells using natural bacterial cellulose/hyaluronic acid as scaffolds for regenerative medicine are presented for the first time in this work. MTT viability assays show higher cell adhesion in bacterial cellulose/gelatin and bacterial cellulose/ hyaluronic acid scaffolds over time with differences due to fiber agglomeration in bacterial cellulose/gelatin. Confocal microscopy images showed that the cell were adhered and well distributed within the fibers in both types of scaffolds. © 2014 Bentham Science Publishers.
Keywords: Bacterial cellulose; Cell viability study; Nanoskin®; Natural nanocomposites; Regenerative medicine; Stem cells